Pengaruh spiritual capital, human capital, structural capital terhadap relational capital dalam meningkatkan performance di perusahaan PT. Shopee - Kumara, Indrawan Dona; Gunawan Putra, Andreas Wahyu (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This objective of the empirical study is to examine and to analyse the influence of spiritual capital, human capital, structural capital on relational capital in increasing performance in PT. Shopee. The sampling procedure used in this study to collect relevant data is to use a questionnaire and use a purposive sampling. This research was conducted on 250 respondents who are employees who work at PT. Shopee at SCBD Jakarta. Data were analyzed using SEM (Structural Equation Modeling) and SPSS (Statistical Program for Social Science) methods. The test results show that Spiritual Capital, Human Capital and Structural Capital have a positive effect on Relational Capital. The findings of this study also show that Performance also has a positive effect on Spiritual Capital, Human Capital, Structural Capital and Relational Capital. In addition, this study also proves that Relational Capital has a positive effect between Spiritual Capital, Human Capital and Structural Capital with Performance.